(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article examines the current methods and approaches used in the diagnosis and treatment of stomach cancer, emphasizing early detection, accurate staging, and personalized therapy. It provides an overview of modern imaging techniques, endoscopic procedures, histopathological analysis, and molecular diagnostics. Furthermore, the study discusses the latest therapeutic strategies, including surgical interventions, chemotherapy, targeted therapy, and immunotherapy. The article highlights the importance of multidisciplinary approaches and the integration of innovative technologies to improve patient outcomes and survival rates.